Does storm duration modulate the extreme precipitation‐temperature scaling relationship?. Issue 20 (29th October 2015) - Wasko, Conrad; Sharma, Ashish; Johnson, Fiona
Abstract: Predicting future precipitation extremes is difficult, and therefore, many studies have used the historical relationship between precipitation intensity and temperature to consider what might occur in a future warmer climate. In general, extreme precipitation intensity is expected to increase as temperatures increase. However, in tropical areas it has been observed that, for higher temperatures, lower precipitation intensities occur, contradicting the expected relationship. This has been thought to be due to limits in moisture availability. In this work we show that the negative scaling found in previous studies may be a result of the analysis methods. By conditioning the precipitation intensity and temperature relationship on storm duration, we demonstrate that positive scaling of precipitation intensity with temperature in tropical regions of Australia is possible. We argue that methods for estimating scaling relationships should be modified to include storm duration. Key Points: Reversal in the scaling of precipitation with temperature in tropical regions Scaling from an aggregation of events may not be representative of individual storm durations Conditioning on storm event duration results in greater scaling